Feeding the future's changing diets: Implications for agricultural markets, nutrition, and policy - Rosegrant, Mark W.; Msangi, Siwa (International Food Policy Research Institute, 2011)
This brief explores the nature of several key drivers of change in food systems and examines a number possible entry points for policy intervention to determine their effect on food prices and other market-driven outcomes.